2016
DOI: 10.7860/jcdr/2016/19020.8437
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Xerostomia in Different Psychological Disorders: An Observational Study

Abstract: A positive association was established between psychological alterations and xerostomia and dryness of lip and mucosa. Emotional alterations may act as a precipitating factor that could influence the salivary secretion resulting in multiple oral diseases. Psychiatrists can screen for xerostomia and collaborate with dentists for comprehensive management of xerostomia in psychiatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 24 publications
2
16
1
Order By: Relevance
“…Results of some studies have indicated that different emotions can decrease or enhance salivary flow [ 7 ]. In addition, psychological disorders, like depression and anxiety, may be associated with xerostomia [ 8 ]. Anxiety and fear can potentially influence saliva secretion through pathways in the amygdala, hypothalamus, and brainstem [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Results of some studies have indicated that different emotions can decrease or enhance salivary flow [ 7 ]. In addition, psychological disorders, like depression and anxiety, may be associated with xerostomia [ 8 ]. Anxiety and fear can potentially influence saliva secretion through pathways in the amygdala, hypothalamus, and brainstem [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, anti-sialogic effects were observed in those taking drugs. 17,25 In this study, multivariate analysis revealed significant associations between xerostomia and medications or therapy, including analgesic NSAIDs, gabapentin, muscle relaxants, psychotherapeutic drugs, and radioactive iodine therapy. Despite the fact that some of the mechanisms remain unknown, medication-induced xerostomia is commonly caused by the altering of neural pathways that stimulate the secretion of saliva.…”
Section: Discussionmentioning
confidence: 65%
“…In another study of young adults, researchers did indicate a difference between the sexes for xerostomia (19.6% in females and 14.6% in males) [21]. Researchers exploring xerostomia in different psychological disorders found more female patients than male patients had xerostomia [22]. They also found nearly half of patients with anxiety and depression, and over a third of patients with schizophrenia had xerostomia [22].…”
Section: Introductionmentioning
confidence: 92%
“…Researchers exploring xerostomia in different psychological disorders found more female patients than male patients had xerostomia [22]. They also found nearly half of patients with anxiety and depression, and over a third of patients with schizophrenia had xerostomia [22].…”
Section: Introductionmentioning
confidence: 99%